2021
DOI: 10.1186/s12883-021-02455-7
|View full text |Cite
|
Sign up to set email alerts
|

The length of susceptibility vessel sign predicts early neurological deterioration in minor acute ischemic stroke with large vessel occlusion

Abstract: Background Patients with acute large vessel occlusion (LVO) presenting with minor stroke are at risk of early neurological deterioration (END). The present study aimed to evaluate the frequency and potential predictors of END in patients with medical management and LVO presenting with minor stroke. The relationship between SVS length and END was also investigated. Methods This was a prospective multicenter study. Consecutive patients were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…44 Further studies on this topic are needed, as a better efficacy of tenecteplase compared to alteplase in larger clots would be of particular importance as larger thrombi have been associated with early neurological deterioration and poor clinical outcomes. 45,46 Our study has several strengths. It is based on two large multicentric LVOS patient registries with similar practices.…”
Section: Discussionmentioning
confidence: 99%
“…44 Further studies on this topic are needed, as a better efficacy of tenecteplase compared to alteplase in larger clots would be of particular importance as larger thrombi have been associated with early neurological deterioration and poor clinical outcomes. 45,46 Our study has several strengths. It is based on two large multicentric LVOS patient registries with similar practices.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion was in line with the present study. Some scholars suggested that endovascular treatments may restore the blood ow thus lower the incidence of ND in patients with minor stroke with steno-occlusive arterial disease [25] .…”
Section: Discussionmentioning
confidence: 99%
“…44 Further studies on this topic are needed, as a better efficacy of tenecteplase compared with alteplase in larger clots would be of particular importance, as larger thrombi have been associated with early neurological deterioration and poor clinical outcomes. 45,46…”
Section: Discussionmentioning
confidence: 99%